Inflation and wages in underdeveloped countries : India, Peru and Turkey, 1939-1960 - Warren, Bill, -1978 (Cass ; Biblio Distribution Center, 1977)
Comparison of national level experience, during inflation, of income redistribution in the manufacturing sectors of India, Peru and Turkey - considers wages and price trends during two decades from 1939, attempts to trace the channels and directions of causality and the effects on the industrialization process, and draws implications for other developing countries. Bibliography pp. 265 to 274, references and statistical tables.